Democracia, globalización y cosmopolitismo - Rascado Pérez, Javier (2016)
At the present time, the traditional conception of democracy has lost its validity and therefore Its characteristic legitimating and tuitive role of rights Product of the transformation of communities, technological development and the various existing social problems.In this article, the author analyzes the historical sources of democracy, its validity and its requirements, seeking to give a new meaning to its concept. Thus, he postulates an answer in cosmopolitanism as the evolution of democracy and solution to current social phenomena.